DETERMINATION OF INITIAL CONDITIONS AND REGIMES FOR IMPLEMENTATION OF STABILIZING CASCADES OF PARACHUTE SYSTEMS OF THE CATAPULT SEAT - Іванов, П. І. (Proceedings of National Aviation University (archive), 2021)
An algorithm for determining the initial conditions and modes in the coordinates velocity - height, velocity pressure - height for calculations of the processes of commissioning of cascadesparachute system catapult chair.